The contribution of the law on the social economy of Galicia to territorial development and the improvement of employment - Bastida, María; Vaquero, Alberto; Cancelo, Maite (REVESCO. Revista de Estudios Cooperativos, 2020)
In recent years, from different institutional levels, and especially within the European Union (EU), there have been recurrent pronouncements regarding the need to accept Social Economy (SE) as a company distinguishing factor, which prioritizes a series of results other than the economic and financial ones. These statements have been accompanied by a recommendation to include this area of the economy in Member States legislation and government policies. At the same time, the recent commitment of the United Nations to the 2030 Agenda, embodied in the Sustainable Development Goals (SDGs), has drawn attention to this area, by aligning the principles and values governing entities. The Galician Autonomous Community was the first to have its own rules on SE. Based on Community and national references, Galicia has had its own legislation in this field since 2016. On the basis of the study of the Autonomous Community Regulation, it should be noted that the special emphasis on two expected results of the regulated institutional framework emerges in a differentiated way: the assignment to the territory and the development of employment. This has a major influence on two objectives common to the SE and the SDGs: the balanced distribution of wealth and the development of quality employment. It also provides solutions to some of the most pressing problems in the complex Galician socio-demographic context. In this paper we study the Galician case as an example of good practices for the promotion and consolidation of the SE fabric, which allows us to face different kind of challenges based on the combination of economic activity and sustainability.
Keywords: Social Economy; Cooperatives; Sustainable Development Goals; Local development Wealth Sharing; High Quality Employment.